Mr. Flagler's St. Augustine. - Graham, Thomas (University Press of Florida, 2014)
Arguably no man did more to make over a city-or a state-than Henry Morrison Flagler. Almost single-handedly, he transformed the east coast of Florida from a remote frontier into the winter playground of America's elite. Mr. Flagler's St. Augustine tells the story of how one of the wealthiest men in America spared no expense in transforming the country's "Oldest City" into the "Newport of the South." He built railroads into remote areas where men feared to tread and erected palatial hotels on swampland. He funded hospitals and churches and improved streets and parks. The rich and famous flock.